Estudo anatômico dos canais mandibular e incisivo com uso de tomografia computadorizada de feixe cônico - Dall'Azen, Gabriel Castro (2020)
This study aimed to identify and analyze the path of the mandibular canal from its entrance in the mandible through the mandibular foramen to its exit through the mental foramen, then going to the mandibular middle line as incisive canal. Cone beam computed tomography (CBCT) from 144 patients were used (50 men and 94 women), which belong to the database of the Dentistry Dental School PUC-RS. It’s a retrospective and observational study with comparative and quantitative analysis of the mandibular reference points viewed on tomographic exams and analysed with On-Demand™ software. In the path of the mandibular canal (MC) and incisive canal (IC) some transversal cuts were made, perpendicular to the mandibular base, and the distance between the dental apices and mandibular cortical were measured in both MC and IC. Comparisons regarding the distances and locations of the canals were made, comparing left and right sides, female and male patients. Women showed bigger proximity between the mandibular canal to dental apices and a smaller distance between the mandibular canal to the mandibular cortical. Men showed smaller distances from the mandibular canal to the lingual cortical as well as a mandibular canal with bigger diameter. Mandibular canal seemed to be closer to the mandibular base in lower second molar region for both men and women. When comparing genders, a considerable amount of measures showed significant difference on the distances analyzed, which didn’t happen when right and left sides of the mandible were compared.